Kecemasan pada Penderita Tuberculosis - Dewi, Bella Ayu Shinta; Sari, Intan Rusdian Permata; Agustin, Dwi; Sari , Selfi Angga (Jurnal Kesehatan, 2022)
Tuberculosis and anxiety are common conditions that impact health problems, both individually and in society. The relationship between tuberculosis and the occurrence of anxiety in Tuberculosis patients is syndemic, which means that the occurrence of tuberculosis is often followed by other health problems such as anxiety. It is therefore important to understand the physiological and social mechanisms associated with these two conditions. The research design used is correlation with cross sectional approach. The sample in this study amounted to 110 respondents, which were taken by total sampling. The results showed that the anxiety of Tuberculosis patients was in the range of mild anxiety to panic. Factors related to the occurrence of anxiety are changes in physical, social conditions and information held by patients related to tuberculosis.